Distribution, habitat use and ecology of deepwater Anemones (Actiniaria) in the Gulf of Mexico - Ammons, A W; Daly, M (Deep-Sea Research. Part II: Topical Studies in Oceanography, 2008)
The distribution of deepwater Actiniaria is poorly known. Rarely are these organisms identified to family, as this requires both well-preserved specimens and taxonomic expertise. Ecological information is similarly lacking. From the results of a comprehensive surveying program in the deep Gulf of Mexico, we report the occurrence of nine species of Actiniaria. For the most abundant four of these, we plot distributions and discuss habitat use, morphological variation, and feeding strategies. Actiniaria in the Gulf appear to have broad, basin-wide distributions with little depth preference. Faunal biomass is highest in the NE Gulf within submarine canyons or at the base of slope escarpments. Attachment mode is mostly opportunistic on various types of hard substrata, including trash. Sediment-dwelling forms are very abundant at an organically rich site within a large submarine canyon.
Keywords: HOV Alvin (Human Occupied Vehicle)